Experience, impact and needs related to urban heat island phenomenon in industrial areas / Alias Ismail - Alias, Ismail (2018)
Many urban and suburban areas experience higher temperatures than their outlying rural surroundings. This difference in temperature is what constitutes an Urban Heat Island (UHI). UHIs result from man-made modifications of the natural environment. The replacement of vegetation, soil and water with concrete, brick, asphalt and metal reduces evapotranspiration, increases the storage and transfer of sensible heat and decreases air movement. Problems that are associated with the urban heat island phenomenon include atmospheric pollution, increased morbidity and mortality, a decreased thermal comfort and an increase in energy consumption. For these reasons, it is desirable to mitigate the UHI effect. Models and tools to predict the effect of UHI mitigation measures can assist the urban planner to incorporate these in urban design. A number of numerical (simulations) and empirical (observational) models have been constructed to date. Empirical models are most likely to be of use to urban planners. However, such a model does not yet exist for Asian country such as Malaysia. As a test bed for a potential, more comprehensive study in the future, the aim of this research is to empirically investigate the experience, impact and needs related to urban heat island phenomenon at industrial area, in terms of land use characteristics, of urban environments in Malaysia (Mont Kiara, Raja Chulan and Setia Alam). Firstly, in order to be able to select relevant data on which the analyses will be conducted, an inventory of UHI mitigation measures has been provided. Mitigation measures of interest have been divided in two categories: vegetation (urban parks and gardens, street trees, green roofs and walls), open water (rivers, ponds, lakes and fountains), built form (low building density and street design that promotes ventilation), material (high albedo materials and porous paving) and anthropogenic sources (improved thermal insulation of buildings and car-free zones). Secondly, the required data has been gathered UHI data has been retrieved from the scientific literature. Three studies, corresponding to three locations, were found to be of use in the analyses. With objective to compile all the information related to basic background, workplace information, workers attitude and experience towards urban heat island, impact and needs to mitigate and improve the precaution and preventive action related to urban heat island phenomenon. Quantitative and qualitative questionnaire used to get the information at selected places stated in scope of works. The interviews conducted will be record in questionnaire and all data will be analyzed by using SPSS (Statistical Package for Social Sciences) software. Data obtained then will be discussed in discussion chapter. Discussion, limitation and conclusion from the research conducted will follow up by further recommendation and future action.